2022
DOI: 10.1186/s12913-022-08224-7
|View full text |Cite
|
Sign up to set email alerts
|

Facilitators and barriers of healthcare workers’ recommendation of HPV vaccine for adolescents in Nigeria: views through the lens of theoretical domains framework

Abstract: Background The human Papillomavirus (HPV) vaccine has demonstrated efficacy in the prevention of cervical cancer when given in early adolescence. The recommendation of the vaccine by health care workers (HCW) is crucial to the uptake of the vaccine by adolescents and the process of this recommendation is important as it determines subsequent uptake of the vaccine. Understanding of the facilitators and barriers of recommendation of this vaccine can help in the development of strategies to improv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
14

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(22 citation statements)
references
References 38 publications
0
8
0
14
Order By: Relevance
“…Regarding the source of information about HPV, a multicenter study with sexually active young adults recruited from 119 Primary Health Care (PHC) services revealed higher scores on knowledge about the virus among participants who were informed via health professionals and the media 23 . The research reinforced the importance of nurses working in these services of adopting communication strategies that favor the dissemination of information, favoring the adherence of this public to vaccination 21 ), ( 26 .…”
Section: Discussionmentioning
confidence: 76%
See 2 more Smart Citations
“…Regarding the source of information about HPV, a multicenter study with sexually active young adults recruited from 119 Primary Health Care (PHC) services revealed higher scores on knowledge about the virus among participants who were informed via health professionals and the media 23 . The research reinforced the importance of nurses working in these services of adopting communication strategies that favor the dissemination of information, favoring the adherence of this public to vaccination 21 ), ( 26 .…”
Section: Discussionmentioning
confidence: 76%
“…Health professionals, in addition to providing information on HPV vaccination, should recommend it to adolescents 14 ), ( 21 ), ( 22 ), ( 23 ), ( 24 ), ( 25 ), ( 26 . Studies show that parents who received the recommendation from a health professional have a higher chance of reporting their intention to vaccinate their children when compared to parents who did not 14 ), ( 26 . Another study, however, revealed that only 64.4% of the parents of girls and 41.6% of the parents of boys received recommendations from health professional regarding the vaccine 27 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…O ajuste foi realizado em virtude de a literatura documentar que meninas se vacinam mais contra o HPV do que meninos (5) , assim, foi possível considerar a influência desse fator sociodemográfico (18) . Para analisar Quanto aos motivos para não terem recebido a vacina, a maioria dos escolares adolescentes do país respondeu "não sabia que tinha que tomar" (46,8%; IC95% 45,4;48,3), seguido pelas respostas "outro motivo" (26,7%;IC95% 25,4;27,9) e "medo de reação à vacina" (7,7%;IC95% 6,9;8,6), respectivamente (Figura 3). (3,5;5,6) 1,2 (0,9;1,5) 6,8 (5,4;8,3) 0,9 (0,7;1,1) 3,3 (2,5;4,1) 0,9 (0,7;1,3) 2,4 (1,6;3,2) 0,7 (0,5;1,1) 3,1 (2,3;3,9) 0,4 (0,3;0,6)* 24,1 (21,9;26,2) 0,9 (0,8;1,0) Sudeste 47,2 (43,8;50,6) 0,9 (0,9;1,0) 3,1 (1,8;4,4) 0,7 (0,4;0,9)* 7,8 (5,8;9,9) 1,1 (0,9;1,4) 3,4 (2,0 ;4,8) 0,9 (0,6;1,4) 3,9 (2,4;5,4) 1,3 (0,9;2,0) 7,8 (5,4;10,3) 1,7 (1,3;2,3)* 25,2 (22,2;28,1) 1,0 (0,9;1,2) Sul 46,3 (42,2;50,4) 0,9 (0,8;1,0) 1,6 (0,5;2,7) 0,3 (0,2;0,6)* 9,7 (6,9;12,5) 1,2 (0,9;1,7) 5,8 (3,5;8,2) 1,3 (0,9;2,0) 3,5 (2,2;4,8) 1,0 (0,7;1,6) 5,5 (3,8;7,3) (10,8;13,7) 0,8 (0,7;0,9)* 36, 4 (34,3;38,4) 1,0 (1,0;1,3) Sudeste 29,6 (25,9;33,4) 0,9 (0,8;1,0) 2,7 (1,6;3,8) 0,9 (0,5;1,3) 13,1 (10,0;16,2) 1,6 (1,2;2,0) 3,1 (2;4,2) 1,2 (0,8;1,7) 3,1 (2,0;4,2) 0,9 (0,6;1,3) 14,1 (10,9;17,3) 1,0 (0,9;1,2) 33,8 (30,4;37,2) 0,9 (0,8;1,1) Sul 24,5 (21,2;27,8) 0,8 (0,7;0,9)* 0,9 (0,2;1,5) 0,3 (0,2;0,6)* 9,2 (7,0;11,5) 0,8 (0,6;1,0) 3,1 (1,8;4,4) 0,9 (0,6;1,4) 7,2 (4,9;9,5) 2,2 (1,6;3,1)* 17,8 (14,7;20,8) 1,3 (1,1;1,5)* 36, 9 (33,4;40,4) 1,1 (1,0;1,2)…”
Section: Brasil 2019unclassified
“…Quanto à fonte de informações sobre o HPV, estudo multicêntrico com adultos jovens sexualmente ativos recrutados em 119 serviços de Atenção Primária à Saúde (APS) revelou maiores escores de conhecimento sobre o vírus entre os participantes que foram informados por profissionais de saúde e pela mídia (23) . A pesquisa reforçou a importância de os enfermeiros que atuam nesses serviços adotarem estratégias de comunicação que privilegiem a divulgação de informações, favorecendo a adesão desse público à vacinação (21,26) .…”
Section: Aspectos éTicosunclassified